Welding simulation of corrugated web girders - Part 2: Effect of manufacturing on shear buckling resistance. (August 2019) - Kollár, D.; Kövesdi, B.
Abstract: Residual stresses and initial geometric imperfections have important effect on the buckling resistance of slender plated steel structures. Despite their large importance, the actual knowledge on residual stresses and exact geometric imperfections are limited, especially for corrugated web girders. In the accompanying paper [1] (Part 1) a finite element model of corrugated web girders is introduced and verified, which is able to virtually simulate the manufacturing process (cold-forming; cutting, welding) of corrugated web girders. The presented numerical model is able to determine the actual imperfection shape and residual stresses which are specific for the actual girder geometry and manufacturing method. The numerical model is further developed for simulating geometrically and materially nonlinear analysis with imperfections (GMNIA) on the virtually manufactured specimens to determine the shear buckling resistance. The effect of manufacturing imperfections on the shear buckling resistance is evaluated for several different corrugation geometries and the obtained tendencies are evaluated and discussed in the current paper. Highlights: The influence of different finite element types and element technologies is presented regarding the shear buckling strength. The applicability of equivalent geometric imperfections recommended by EN 1993-1-5:2006 is presented. An advanced numerical model has been developed to simulate virtual testing of previously manufactured specimens. The influence of residual stresses and initial geometrical imperfections on shear buckling strength is evaluated. The simulated shear buckling strengths are compared with formulae developed for hand calculations.